KAJIAN BAHASA SLANGA REMAJA DUSUN DI KOTA BELUD, SABAH : SATU ANALISIS SOSIOLINGUISTIK - RACHEL ARORA, NUAIT (Universiti Malaysia Sarawak (UNIMAS), 2020)
This study aims to study the lexical slang amongst Dusun teenagers and the context of the language use in Kota Belud, Sabah. In particular, the objective of the study is to identify the lexical language of Dusun slang and the use of slang language based on selected domains. Fishman’s domain approach (1965) was adopted for this purpose. This study uses online interview methods and questionnaires to collect data. A group made of 20 informants are selected for interview and 100 respondents completed the the questionnaires. The findings of the study showed that 20 lexicals were identified through interviews while 43 slang lexical were identified through questionaaires making the total slang are 63 lexical. From the 3 domains, a total of 21 slang lexical are used in family domain, 12 in friend domain and 10 in school domain. The results showed that the use of slang in the family domain had the highest number while the use of slang in the school domain was the lowest. This study is important to fill in the gaps of past studies that are seen to be insufficient to elaborate in detail. The results of the study have highlighted the language style and certain expressions of Dusun’s teenagers in Kota Belud in expressing slang according to the selected domains